Series/Festivals - Papademas, Diane (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
A list of film festivals: Series and festivals may be offered and developed, bridging communities campus, and curricular programs. The world’s film industry has gurgeoned over the last decade on all levels, commercial and independent enterprises, with serious, social issue films reaching larger audiences. The distributors list in this volume conveys a sense of range and volume, which can faciliatate scheduling thematic series. Listed here are number of completed films and their diversity of style and content. Finding visual media with pedagogical utility can be enjoyable experience, going to festivals or bringing traveling festivals to you.